Eksistensi Kesenian Jaranan Gembong Bawono di Sentang Kabupaten Asahan - Desy Wulan Pita Sari Damanik (UNIVERSITAS STEKOM, 2024)
Jaranan Gembong Bawono art is a traditional art that developed in Asahan Regency, North Sumatra. The Javanese tribe, which makes up the majority of the population in this district, influences the existence and occurrence of artistic activities. The times have influenced the existence of this traditional art in the Asahan Regency area. Jaranan art is a traditional art that always maintains ancestral values ​​and its main function. To maintain the existence of jaranan art, the Gembong Bawono Association made a change which ensures that this art still exists. This research aims to describe the existence of Jaranan Gembong Bawono art in Kisaran Timur District, Asahan Regency. The approach used in this paper is the existential approach. Soren Kierkagaard divides human existence into three levels, each of which has distinctive characteristics, namely aesthetic existence, (2) ethical existence, (3) religious existence. To deepen the existence of jaranan art, the concept of sociological theory was borrowed. Data collection used interviews, observation and documentation by analyzing the existence of the Gembong Bawono jaranan in Kisaran Timur District, Asahan Regency using descriptive methods, which is qualitative research. The research uses ethnographic methods from James P. Spradley's book. Ethnography consists of research techniques, ethnographic theory, and various kinds of describing culture. With this research, we can find out the existence of Jaranan Gembong Bawono among the people of Kisaran Timur District, Asahan Regency. Then so that it can be transmitted in written form by the next generation. The form of dance movements in this art is dynamic and strong, with the prominent addition of accompaniment which is very influential on the dance. These two components are processed into a unified whole.